"Third Party Contingency" contracts in settlement and litigation - Roland Kirstein; Neil Rickman (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2002)
We present, for the first time, a model of recent institutional developments in litigation funding across several European jurisdictions. Recognizing the financing constraints that British cost rules may impose on litigants, these new contractual arrangements combine contingency fees with third party cover for cost in the event of losing the case: we call these ?Third Party Contingency? (TPC) contracts. Signing a TPC contract can make filing a suit credible and may increase settlement amounts. This does not, however, increase the likelihood of going to trial, since TPC contracts are only of mutual benefit to the plaintiff and the third party when the case settles out of court. We also find that the mere availability of TPCs may generate the above strategic effect. – – Das Paper enthält die erste Analyse einer neuen Institution zur Prozeßkostenfinanzierungs im Bereich der "britischen" Regel: Verträge, bei denen eine dritte Partei dem Kläger zusagt, im Falle der Klageabweisung die gesamten Prozeßkosten zu tragen. Im Gegenzug erhält diese dritte Partei einen Teil der durch Vergleich oder Urteil vom Beklagten erlangten Summe. Solche "TPC Verträge" (third party contingency contracts) überwinden die finanziellen Hürden bei der gerichtlichen Verfolgung von Ansprüchen. Sie machen die Drohung mit einer Klage auch dann glaubwürdig, wenn (ohne TPC Vertrag) der erwartete Wert des Prozesses für den Kläger negativ wäre. Dadurch erhöhen sie die Vergleichsbereitschaft des Beklagten und die Vergleichszahlungen. Wir zeigen, daß schon die reine Verfügbarkeit von TPC Verträgen diesen strategischen Effekt erzeugen könnte.
Keywords: G22; K41; C7; 330; Contingent fees; British cost allocation rule; Legal Cost Insurance; strategic moves; Gerichtliche Prozesskosten; Rechtsschutzversicherung; Erfolgsbeteiligung; Vertragstheorie; Verhandlungstheorie; Theorie